2020
DOI: 10.1016/j.cjco.2020.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Canadian Real-World Experience of Using Sacubitril/Valsartan in Patients With Heart Failure With Reduced Ejection Fraction: Insight From the PARASAIL Study

Abstract: Background To determine the effectiveness of sacubitril/valsartan 97/103 mg twice daily (b.i.d.) on tolerability, safety, and quality of life (QoL) in Canadian patients with heart failure with reduced ejection fraction in a real-life setting. Methods In P rospective, Multicenter, Open L a bel, Post-App r ov a l S tudy Ai … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
7
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 23 publications
9
7
0
1
Order By: Relevance
“…This appears similar to the 35.7% of patients reported at 7 months in a non-selected cohort, 32 but low compared with a further report mentioning >60% of the patients with a 97/103 mg SV dosage at 6 months. 31 We also report that 12.65% of our patients presented an SV-associated hypotension, which is similar to the fraction (10.3%) reported in the PARASAIL study. 31 Only 3.80% of our whole population presented a 30% decrease in eGFR in comparison, which is quite comparable with the 3.03% reported by Pharithi et al 35 Limits and strengths of the study A limit, but also a strength, of our study is the real-life design.…”
Section: Safetysupporting
confidence: 90%
See 2 more Smart Citations
“…This appears similar to the 35.7% of patients reported at 7 months in a non-selected cohort, 32 but low compared with a further report mentioning >60% of the patients with a 97/103 mg SV dosage at 6 months. 31 We also report that 12.65% of our patients presented an SV-associated hypotension, which is similar to the fraction (10.3%) reported in the PARASAIL study. 31 Only 3.80% of our whole population presented a 30% decrease in eGFR in comparison, which is quite comparable with the 3.03% reported by Pharithi et al 35 Limits and strengths of the study A limit, but also a strength, of our study is the real-life design.…”
Section: Safetysupporting
confidence: 90%
“…31 We also report that 12.65% of our patients presented an SV-associated hypotension, which is similar to the fraction (10.3%) reported in the PARASAIL study. 31 Only 3.80% of our whole population presented a 30% decrease in eGFR in comparison, which is quite comparable with the 3.03% reported by Pharithi et al 35 Limits and strengths of the study A limit, but also a strength, of our study is the real-life design. Although randomized controlled trials are the gold standard for evaluating treatment effects, they may not always fully represent what happens in real life because of inherent selection bias.…”
Section: Safetysupporting
confidence: 90%
See 1 more Smart Citation
“…The QoL improvement with sac/val treatment is an important issue and, according with this, in PARADIGM-HF it occurred early after 8 months as demonstrated by increase in KCCQ (McMurray JJ, et al, 2014) and this finding has been also reported in different real life settings so as Parasail study and Provide-HF (Haddad H, et al, 2020;Mentz RJ, et al, 2020) after a follow-up of 12 weeks and 12 months, respectively. Our study shows more consistent data because the QoL improvement rises up at 6 months by the start of the treatment with sac/val and it persists over 24 months.…”
Section: Discussionmentioning
confidence: 82%
“…The potential reverse remodelling effect of sac/val has been demonstrated in the PRIME study, a prospective randomized trial showing that sac/val is more effective than the only angiotensin receptor blocker to improve functional mitral regurgitation HF associated after 12 months of follow-up, without significant changes in LVEF (Kang DH, et al, 2019). Moreover, several real world evidence studies have reported an improvement of cardiac remodelling markers and patients' functional capacity (Spannella F, et al, 2019;Moliner-Abós C, et al, 2019;Wachter R, et al, 2019;Haddad H, et al, 2020;Mentz RJ, et al, 2020;Correale M, et al, 2020;Cosentino et al, 2019;Martens P, et al, 2018). In particular, a retrospective cohort study on a small number of HFrEF patients showed, after a mean follow-up of 14 months, a significant improvement in LVEF and GLS (De Vecchis R, et al, 2019).…”
Section: Discussionmentioning
confidence: 99%